PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN KETERAMPILAN MEMBACA TEKS NEGOSIASI SISWA KELAS X JURUSAN GEOLOGI PERTAMBANGAN SMK NEGERI 6 SAMARINDA TAHUN PEMBELAJARAN 2016/2017 - Fitri Prima Nurani (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
This study aimed to improve negotiation text reading skill so that students’ learning achievement and reading skill of negotiation text in Indonesian language and literature can reach the minimum mastery standard . It used (1) observation, (2) questionnaire, and (3) test in collecting the data . It was qualitative research that applied descriptive statistics . This analysis was only an accumulation of basic data in the form of descriptions that did not seek or explain any mutual relationships, did not test any hypotheses, and did not make any predictions or conclusions .